The Influence of TikTok Viral Marketing on Online Purchase Decisions of Implora Lipstick: The Mediating Role of Brand Awareness - Putri, Chintya Tiara; Koeswandi, Tika Annisa Lestari; Rahmani, Nizza Nadya (The Future of Education Journal, 2025)
This study aims to analyze the influence of viral marketing on the TikTok platform on purchase decisions for Implora lipstick products, with brand awareness serving as an intervening variable. The research background stems from the phenomenon of high exposure to Implora content on TikTok, which has not yet aligned with an optimal level of purchase conversion . This highlights the importance of understanding the role of brand awareness as a bridge between viral marketing and purchase decisions. This study employs a quantitative method with a survey approach. Data were collected through the distribution of questionnaires to 150 respondents, consisting of TikTok users in West Java who are familiar with Implora products . The sampling technique applied was purposive sampling. Data analysis was conducted using mediation testing with SmartPLS version 4 software. The results indicate that viral marketing has a positive and significant effect on both brand awareness and purchase decisions. Additionally, brand awareness is proven to have a positive and significant influence on purchase decisions . Key findings demonstrate that brand awareness significantly mediates the relationship between viral marketing and purchase decisions. This implies that viral content on TikTok is far more effective in driving purchases when it successfully builds strong brand awareness in the minds of consumers first.